Matrix metalloproteinase 9 is associated with peritoneal membrane solute transport and induces angiogenesis through β-catenin signaling. Issue 1 (4th May 2016) - Padwal, Manreet; Siddique, Imad; Wu, Lili; Tang, Katelynn; Boivin, Felix; Liu, Limin; Robertson, Jennifer; Bridgewater, Darren; West-Mays, Judith; Gangji, Azim; Brimble, Kenneth Scott; Margetts, Peter J.
Abstract : Background. For patients using peritoneal dialysis (PD), the peritoneal membrane can develop fibrosis and angiogenesis, leading to ultrafiltration failure, chronic hypervolemia and increased risk of technique failure and mortality. Matrix metalloproteinases (MMPs), and specifically the gelatinases (MMP2 and MMP9), may be involved in peritoneal membrane injury. Methods. From stable PD patients, mesothelial cells were assayed for MMP gene expression. MMP9 was overexpressed in mouse peritoneum by adenovirus, and MMP9 −/− mice were subjected to transforming growth factor β (TGF-β)–induced peritoneal fibrosis. Results. MMP9 mRNA expression correlated with peritoneal membrane solute transport properties. Overexpression of MMP9 in the mouse peritoneum induced submesothelial thickening and angiogenesis. MMP9 induced mesothelial cell transition to a myofibroblast phenotype measured by increased alpha smooth muscle actin and decreased E-cadherin expression. Angiogenesis was markedly reduced in MMP9 −/− mice treated with an adenovirus expressing active TGF-β compared with wild-type mice. TGF-β-mediated E-cadherin cleavage was MMP9 dependent, and E-cadherin cleavage led to β-catenin-mediated signaling. A β-catenin inhibitor blocked the angiogenic response induced by AdMMP9. Conclusions. Our data suggest that MMP9 is involved in peritoneal membrane injury possibly through cleavage of E-cadherin and induction of β-catenin signaling. MMP9 is a potential biomarker for peritoneal membrane injury and is a therapeutic target to protect the peritoneal membrane in PD patients.